Environmental Encyclopedia - Blanchfield, Deirdre S., editor 652396; Gale Group (Online service) 651863 (Detroit : Gale, 2011)
Provides in-depth, worldwide coverage of environmental issues. Each article is written in a nontechnical style and provides current status, analysis, and suggested solutions whenever possible.